27‐Hydroxycholesterol enhanced osteoclastogenesis in lung adenocarcinoma microenvironment. Issue 8 (3rd December 2018) - Zhang, Lishan; Liu, Ming; Liu, Jinglei; Li, Xingkai; Yang, Ming; Su, Benhua; Lin, Yanliang
Abstract: 27‐Hydroxycholesterol (27‐HC) has been implicated in the pathological process of estrogen receptor positive breast cancer. However, the role of 27‐HC in lung adenocarcinoma is still unclear. Because bone metastasis is a main reason for the high mortality of lung adenocarcinoma, this study aimed to investigate the effect of 27‐HC on osteoclastogenesis in lung adenocarcinoma microenvironment. The results showed that the conditioned media (CM) from lung adenocarcinoma cells cocultured with macrophages promoted osteoclast differentiation, which was enhanced by 27‐HC. Further investigation showed that CM inhibited miR‐139 expression and promoted c‐Fos expression. Luciferase reporter assay identified c‐Fos as a direct target of miR‐139. CM also induced the expression and nuclear translocation of NFATc1 and STAT3 phosphorylation, which was enlarged by 27‐HC but was attenuated by miR‐139. Coimmunoprecipitation assay demonstrated that 27‐HC increased the interaction between NFATc1 and phosphorylated STAT3, which was restricted by miR‐139. Chromatin immunoprecipitation assay showed that pSTAT3 could bind to the promoter of c‐Fos, c‐Fos could bind to the promoter of NFATc1, and both pSTAT3 and NFATc1 could bind to the promoter of Oscar, which were enlarged by 27‐HC but were blocked by miR‐139. Knockdown of c‐Fos mimicked the effect of miR‐139. These results suggested that CM, especially containing 27‐HC, promoted osteoclastogenesis by inhibiting miR‐139 expression and activating the STAT3/c‐Fos/NFATc1 pathway. Abstract : 27‐Hydroxycholesterol (27‐HC) enhanced osteoclast differentiation from RAW267. Four cells cultured in conditioned media (CM) from A549 cells and macrophages. 27‐HC enhanced the inhibitory effect of CM on the miR‐139 expression and the stimulating effect of CM on the STAT3/c‐Fos/NFATc1 pathway.